Diversity and Versatility in Small RNA-Mediated Regulation in Bacterial Pathogens - Felden, Brice; Augagneur, Yoann (Frontiers in Microbiology, 2021)
Bacterial gene expression is under the control of a large set of molecules acting at multiple levels. In addition to the transcription factors already known to be involved in global regulation of gene expression, small regulatory RNAs (sRNAs) are emerging as major players in gene regulatory networks, where they allow environmental adaptation and fitness. Developments in high-throughput screening have enabled their detection in the entire bacterial kingdom. These sRNAs influence a plethora of biological processes, including but not limited to outer membrane synthesis, metabolism, transcription factor regulation, transcription termination, virulence, and antibiotic resistance and persistence. Almost always noncoding, they regulate target genes at the post-transcriptional level, usually through base-pair interactions with mRNAs, alone or with the help of dedicated chaperones. There is growing evidence that sRNA-mediated mechanisms of actions are far more diverse than initially thought, and that they go beyond the so-called cis- and trans-encoded classifications. These molecules can be derived and processed from 5′ untranslated regions (UTRs), coding or non-coding sequences, and even from 3′ UTRs. They usually act within the bacterial cytoplasm, but recent studies showed sRNAs in extracellular vesicles, where they influence host cell interactions. In this review, we highlight the various functions of sRNAs in bacterial pathogens, and focus on the increasing examples of widely diverse regulatory mechanisms that might compel us to reconsider what constitute an sRNA.